Divine Simplicity, Divine Relations, and the Problem of Robust Persons - Campbell, Ronnie (Religions, 2024)
In this paper, I aim to defend a robust concept of “person” as it relates to the Christian doctrine of the Trinity. I begin by situating the debate in the current context between Social Trinitarianism (ST) and Latin Trinitarianism (LT) and then zero in on Thomas Aquinas’s view of the divine Persons as subsistent relations. I will argue that such an understanding of divine Persons has two significant difficulties. First, Aquinas’s view of a strong doctrine of divine simplicity is susceptible to modal collapse. For on such a view, there are no real distinctions within God; such distinctions are conceptually only. If there are no real distinctions within God, then how can we make sense of the eternal relations within God? Second, I question whether a relation can be equated with a Person. After all, relations do not know things, perform actions, or love in the way Scripture portrays the divine Persons. I will then offer a constructive and more robust view of the divine Person—one that aligns with the control of Scripture. In doing so, I consider two objections, one centering on whether defenders of ST fall into tri-theism and the other on whether divine Persons can indeed work together.